AI Thumbnails on YouTube for MSME Brands: A Study on GETI Media SME Live - Edy Chandra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2025)
This study evaluates the effectiveness of AI-generated or AI-assisted thumbnails in enhancing content performance and reinforcing visual branding on the educational YouTube channel